Ornithosymbols of the Kalmyk Language: Thanatological Aspect - Lidzhiev, Alexander B. (2021)
This article is devoted to the ethnolinguistic study of the bird symbolism in the culture of Kalmyks and other Mongolian peoples. The work presents the main characteristics of bird symbolism, reflecting the most common images in the conceptions of Kalmyks, however, the main attention is paid to the thanatological aspect, this is due to the special specifics and a number of stereotypes in perception of some bird species. The most widespread thanatological symbol in the Kalmyk language and in the culture of the Mongol peoples dedicated to death is the raven and the owl. The objective of the work is to conduct an ethnolinguistic study of thanatological symbolism of birds in the Kalmyk culture, which is based on folklore and ethnographic material. The methodology of the study has been a complex method, which involves a comprehensive study of the material. The result of the work shows that traditionally, the Mongolian peoples have developed a set of symbols that are the most significant and revered. Signs and superstitions allow us to reconstruct the ethnic picture of the world and have a pronounced ethnocultural specificity, in which the experience of the people and stereotypes of ethnic consciousness are concentrated.